Assessment of chronic liver disease using two-dimensional shear wave elastography in a tertiary care hospital in North India - Raunak Rishu; Shagufta Wahab; Khwaja S. Zafar; Rizwan A. Khan (MGM Journal of Medical Sciences)
Background: Chronic liver disease (CLD) presents a significant public health challenge, often leading to cirrhosis and severe fibrosis. Common causes include viral hepatitis, excessive alcohol consumption, and non-alcoholic fatty liver disease, among others. This study evaluated liver stiffness using two-dimensional shear wave elastography (2D-SWE) in patients with CLD at a tertiary care center in northern India. Materials and Methods: This prospective study was conducted in the Department of Radiodiagnosis at Jawaharlal Nehru Medical College and Hospital, Aligarh Muslim University, Aligarh, Uttar Pradesh, India, from July 2022 to June 2024. One hundred patients diagnosed with CLD, and 100 age-matched healthy controls were included. Liver stiffness was measured using a Samsung V8 ultrasound system with 2D-SWE techniques, and the liver stiffness values were expressed in kilopascals (kPa) and graded accordingly. Results: Liver stiffness was significantly elevated in the CLD group, with a mean value of 14.09 kPa compared to 4.95 kPa in the control group. The median and interquartile range values also indicated statistically significant differences (P < 0.001). Among the CLD patients, 41% exhibited Grade 2 fibrosis, 41% exhibited Grade 3, and 18% showed Grade 4 fibrosis. In contrast, 83% of the control group displayed no fibrosis, while 17% had Grade 1 fibrosis. Conclusion: Two-dimensional SWE is a reliable, non-invasive tool for assessing liver stiffness and staging fibrosis in CLD. It evaluates a larger liver volume than a conventional biopsy without the risk of hemorrhage or infection. This technique holds promise for the routine assessment and monitoring of liver fibrosis.